A facile and low-cost wet-chemistry artificial interface engineering for garnet-based solid-state Li metal batteries. (October 2022) - Leng, Jin; Liang, Hongmei; Wang, Huaying; Xiao, Zunqiu; Wang, Shitong; Zhang, Zhongtai; Tang, Zilong
Abstract: Solid-state lithium metal batteries (SSLMBs) have been widely predicted as an "enabler" for the next-generation high-energy-density batteries. To perform this goal, both solid electrolytes (SEs) and metallic Li anodes are the keys. Li-rich garnet SEs exhibit many unique advantages for enabling SSLMBs, such as high Li-ion conductivity, superior mechanical, chemical and electrochemical properties. However, the garnet-based SSLMBs suﬀer from intractable interfacial problems including poor-contact-induced high interfacial impedance and dendrite-induced fast short circuit, which greatly hinder their practical application. In this work, a facile and low-cost artificial interface engineering is proposed to improve Li/SEs interface. Benefitted from the superior wettability of isopropanol InCl3 solution on the Li6.4 La3 Zr1.4 Ta0.6 O12 (LLZTO) surface, a homogeneous and tightly-adhering lithiophilic interface consisting of InLi x and LiCl is efficiently constructed. As a result, the interface impedance was decreased from 189 to 10 Ω, and the critical current density for the LLZTO is increased from 0.2 mA cm −2 to 0.7 mA cm −2 . The Li/Li symmetric cells can work stably above 4000 h at a current density of 0.2 mA cm −2 . At a higher current density of 0.45 mA cm −2, no obvious dendritic Li proliferation and interfacial contact failure is observed after cycling for more than 1000 h. The full cells with LiFePO4 as cathode exhibit a superior electrochemical performance with a reversible capacity of 127 mAh g −1 at 0.5 C after 475 cycles, and a rate capability of 101 mAh g −1 at 1 C. This eﬀective, simple and economical wet-chemistry strategy for constructing Li/SEs artificial interface may provide an alternative route for solve the interfacial issues of other SSLMBs. Graphical Abstract: ga1 Highlights: A facile and low-cost wet-chemistry enables robust Li/LLZTO artificial interface. The keys for this wet-chemistry strategy: solvent, active solute and H2 O content. The InCl3 -induced modification layer significantly improve cells' performance. This adaptable technique may be applicable to other solid Li metal batteries.